How to Assist Probationers with Debt Problems during Supervision? A Qualitative Study into the Experiences of Both Probation Officers and Clients - van Beek, Gercoline (Crime & delinquency, 2022)
Little research exists on what works in the supervision of offenders with debt problems. This qualitative study aims to provide insight into the barriers probation officers and clients experience during supervision regarding debt and the support that clients need. Interviews were conducted with 33 Dutch probation officers and 16 clients. The results show that debt often negatively influences clients? lives and hinders their resocialization. Probation officers lack effective methods to support clients with debt problems. To adequately help clients with debt problems, probation officers should obtain more knowledge about effective interventions and collaborate more closely with debt specialists from the probation supervision outset.